Corporate Finance and the Monetary Transmission Mechanism - Bolton, Patrick; Freixas, Xavier (Review of Financial Studies, 2006)
We analyze the transmission effects of monetary policy in a general equilibrium model of the financial sector, with bank lending and securities markets. Bank lending is constrained by capital adequacy requirements, and asymmetric information adds a cost to outside bank equity capital. In our model, monetary policy does not affect bank lending through changes in bank liquidity; rather, it operates through changes in the spread of bank loans over corporate bonds, which induce changes in the aggregate composition of financing by firms, and in banks' equity-capital base. The model produces multiple equilibria, one of which displays all the features of a "credit crunch."